Towards a people's culture - Staal, Jonas; Sison, Jose Maria (New World Academy Reader, 2013)
"New World Academy (NWA) invites progressive political organizations to share with artists and students their views on the role of art and culture in political struggles. Together, they engage in critical thinking through concrete examples of transformative politics and develop collaborative projects that question and challenge the various frameworks of justice and existing models of representation. NWA proposes new critical alliances between art and progressive politics, as a way to confront the democratic deficit in our current politics economy, and culture." -- Provided by publisher